AB0307 Overlooking severe infections during tocilizumab therapy for the rheumatic diseases. (23rd January 2014) - Kikuchi, E.; Suzuki, A.; Uekubo, K.; Aoki, N.; Yoshioka, T.; Ishiyama, Y.; Okai, T.
Abstract : Background: When patients with rheumatic disease get severe infections while being treated by tocilizumab (TCZ), body temperature, white blood cells (WBC) and CRP often would be kept normal by the inhibition of IL-6. It is a concern that patients who got severe infections (the condition that requires hospitalization) may be overlooked and instructed to return home. Objectives: In our center, we evaluated how the patients who required hospitalization because of severe infections were overlooked at the initial visit to the rheumatology clinic or ER during TCZ therapy. Methods: From the total of 38 rheumatic disease patients in TCZ therapy (Rheumatoid arthritis 36 cases, adult onset Still's disease 1 case, multicentric Castleman's disease 1 case, the mean age at TCZ start 62.9 ± 15.0 yo, all patients were treated with 8mg/kg), we examined 13 cases who got hospitalization by diagnosis of infectious disease (bacterial pneumonia 3 cases, urinary tract infection 2 cases, cellulitis 2 cases, Pneumocystis pneumonia 2 cases and others 4 cases). The 8 patients were admitted directly from the first visit to the unit (clinic or ER) with complaint about the infection ( immediate admission group ). The other 5 patients were instructed to go home at the first visit even having a complaint but were admitted due to infection at a later date ( delayed admission group ). We analyzed the clinical data of the two groups. Results: Ages at the admission were similar in both groups (immediate admission group: 75.8 ± 4.4 yo vs. delayed admission group: 72.2 ± 4.9 yo). All the patients were over 65 years old. At the first visit for signs of infection, there was no significant difference in body temperature (36.9 ± 0.8 degree Celsius vs. 36.3 ± 0.4 degree Celsius), WBC (6888 ± 2976 /μl vs. 7680 ± 2027 /μl), CRP (1.42 ± 2.18 mg/dl vs. 1.94 ± 2.38 mg/dl), and the treatment period of TCZ (7.8 ± 7.0 months vs. 8.1 ± 7.6 months). There is also no significant difference in length of hospital stay (27.3 days vs. 26.4 days). The all 8 patients in immediate admission group complained of fever or some focal symptoms such as dyspnea, cough, joint pain or leg pain. Admissions were determined at the time of ER visits in 4 cases but there were no overlooked severe infection cases at the ER visits. The 4 patients out of 5 in delayed admission group complained almost only of fatigue at the day of scheduled rheumatology outpatient visits but were admitted later within 1 week due to infection. One patient died during the hospitalization in the delayed admission group. Conclusions: Although the number of the cases is limited, overlooking severe infections with tocilizumab treatment in our center mainly occurred during regular visits to the rheumatologist and complaining of fatigue only. We think it is difficult to evaluate whether the patient required hospitalization from clinical data only. Even if fatigue is the only complaint for the patients treated with TCZ, we need to pay careful attention and consider hospitalization. References: Campbell, et al: Risk of adverse events including serious infections in rheumatoid arthritis patients treated with tocilizumab: a systemic literature review and meta-analysis of randomized controlled trials. Rheumatology. 2011; 50: 552-62 Disclosure of Interest: None Declared